An azo-coupling reaction-based surface enhanced resonance Raman scattering approach for ultrasensitive detection of salbutamol. Issue 10 (1st February 2018) - Yu, Shihua; Liu, Zhigang; Zhang, Jianpo; Li, Hongwei; Xu, Na; Yuan, Xin-xin; Wu, Yuqing
Abstract : Azo-coupling reaction-based SERRS indirect approach for SAL detection, with a LOD of 1.0 × 10 −11 M within 7 min for real samples. Abstract : To date, great achievements with GC-MS, HPLC-MS, and fluorescence biosensing techniques have been made to detect illegal additives of salbutamol (SAL) in swine meat. However, these methods are not suitable for rapid on-site screening due to either costly instruments or rather complicated and/or time consuming sample pretreatments. Herein, a simple, rapid and ultrasensitive approach based on an azo-coupling reaction and surface-enhanced resonance Raman scattering (SERRS) is presented. By combining with a magnetic SERS substrate, an indirect detection for SAL, with a LOD of 1.0 × 10 −11 M (2.39 pg mL −1 ), was realized. Moreover, a colorimetric method for naked eye detection was successfully carried out for rapid screening of SAL in concentrations higher than 2.09 × 10 −5 M (5 μg mL −1 ). In addition, the proposed method was successfully applied for the rapid determination of SAL in real swine meat. The entire process, including pretreatment, coupling reaction and SERRS detection, was performed within 7 min. Moreover, the SERRS fingerprint band being specific to corresponding functional group guarantees the selectivity for the target molecule. Therefore, the proposed strategy in the present study offers a new way to identify trace amounts of analytes, such as SAL as well as other illegal additives in health-related products and food.